From Greed to Conscience: Framing a Global System that Works for Everyone (Global Journal of Human-Social Science, 2019)
Trading to benefit self and unintentionally others became the most revolutionary idea over the past 200 years. It has become not only the core of the global economic system but a creed and way of life. This system is the free-market neoliberalism. But its perils are increasing by the day. Free-market health sector reforms in Uganda and other countries are the cause of health service deterioration not only in Uganda but around the world. Health service crisis in low-income countries is part of a bigger global crisis arising from free-market policies. These crises include the widening economic disparity, an increasing number of poor, hungry and angry people around the world; rising tensions and restlessness, terrorism, mass migration, and unemployment. The earth's natural resources are depleting and ecosystems degrading, resulting in loss of biodiversity, arable land, and water systems. This situation is causing adverse climate change and less than adequate food production. In the face of these challenges, the values of free-market capitalism is becoming untenable and obsolete. A new civilization is emerging and we, the current generation, should guide it with the values of sustainable economic production, equitable wealth distribution, elimination of deprivation, living within the earth's carrying capacity, and human fulfillment. Indeed consensus is now building up to a world-wide compact for a new civilization.